COMPOSITIONAL VARIATIONS OF Au-Ag TELLURIDE MINERALS OF ARINEM DEPOSIT, WEST JAVA - Euis Tintin Yuningsih (Jurnal Geologi dan Sumberdaya Mineral, 2011)
The epithermal Arinem veins system of gold-silver-base metal mineralization is located in the Arinem area in the southwestern part of Java Island, Indonesia. The veins are composed predominantly of quartz+calciteÂ±illiteÂ±kaolinite with variable amount of manganese oxide and limonite and high amount of sulfides. The deposit contains a number of Te-bearing minerals, notably tellurides and tellurosulfide minerals. The tellurium mineral assemblages in the Arinem and Bantarhuni veins are similar in the presence of hessite (Ag2Te), petzite (Ag3AuTe2), stutzite (Ag5Te3), tetradymite (Bi2Te2S) dan altaite (PbTe). The tellurium mineral assemblages vary from sample to sample and most of the observed telluride occurrences consist of at least 2 different phases (e.g. petzite-hessite, tetradymite-hessite, petzite-hessite-altaite). Gold concentrations measured in Te-mineral of petzite from the Arinem vein are in the range between 14.24 to 18.32 wt%. Some hessite and stutzite contain gold up to 3.48 and 1.10 wt%, respectively. Some of electrums are present as inclusions in Te-mineral patches in both veins.Keywords : Electrum, petzite, sulfide, tellurides, Arinem, Bantarhuni